Unravelling the Mysteries of Africa's Underdevelopment Changing Africa, One Idea at a Time - Forje, John W. (Book collections on Project MUSE., 2020)
Unravelling the mysteries of Africa's underdevelopment presents an Afrocentric ideological understanding of the continent's fragmentation; a scientific and objective (Mijadala) discourse as well as an approach of how to move progressively and sustainably Africa forward. The breadth and depth of the book shows the unwavering impoverishment and urgent need for the continent to stand up and take the bull by the horn. It offers an inspiring means of grappling with the continent's problems to build the change we want - An African Wealth of Nation - not the continent of collapsed, failed states under the governance construct of centralised authoritarian regimes It is a thought-provoking discourse that challenges us all to be inherent participants in the reconstruction of a Brave New Africa far beyond the 21st Century.